Mortality impact of low annual crop yields in a subsistence farming population of Burkina Faso under the current and a 1.5°C warmer climate in 2100 - Belesova, Kristine; Sauerborn, Rainer (The science of the total environment, 2019)
In subsistence farming populations of sub-Saharan Africa reliant on rainfed agriculture, years of low crop yields result in poorer child nutrition and survival. Estimates of such impacts are critical for their reduction and prevention. We developed a model to quantify such health impacts, and the degree to which they are attributable to weather variations, for a subsistence farming population in the Nouna district of Burkina Faso (89,000 people in 2010). The method combines data from a new weather-crop yield model with empirical epidemiological risk functions. We quantify the child mortality impacts for 1984-2012 using observed weather data and estimate potential future burdens in 2050 and 2100 using daily weather data generated by global climate models parameterized to simulate global warming of 1.5°C above pre-industrial levels. For 1984-2012, crop yields below 90% of the period average were estimated to result in the total of 109.8 deaths per 10,000 children <5years, or around 7122.0years of life lost, 72% of which are attributable to unfavourable weather conditions in the crop growing season. If all non-weather factors are assumed to remain unchanged, the mortality burden related to low crop yields would increase about twofold under 1.5°C global warming by 2100. These results emphasize the importance and value of developing strategies to protect against the effects of low crop yields and specifically the adverse impact of unfavourable weather conditions in such settings under the current and future climate.
Gesehen am 21.01.2020